2016
DOI: 10.3765/salt.v26i0.3863
|View full text |Cite
|
Sign up to set email alerts
|

Causal necessity and sufficiency in implicativity

Abstract: Karttunen's (1971) implicative verbs are notable for generating inferences over their complements. English manage to X, for instance, entails the truth of X: the entailment reverses with matrix negation and seems tied to the elusive presuppositional contribution of the implicative predicate (Coleman 1975). Building on Baglini & Francez (2015), and drawing on implicative data from Finnish, I propose an account of the implicative class which links the lexical presuppositional content of an implicative verb to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Our data support an analysis where most examples of orka reflect two meaning components: participant-internal ability and sufficiency of mental or physical strength. In line with Nadathur's (2016) proposal for the semantic profile of Finnish jaksaa, a verb similar to orka, we suggest that the sufficiency component of orka reflects an assumed obstacle, i.e. the presence of sufficient strength/energy, to the event reflected in orka's complement.…”
Section: Concluding Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our data support an analysis where most examples of orka reflect two meaning components: participant-internal ability and sufficiency of mental or physical strength. In line with Nadathur's (2016) proposal for the semantic profile of Finnish jaksaa, a verb similar to orka, we suggest that the sufficiency component of orka reflects an assumed obstacle, i.e. the presence of sufficient strength/energy, to the event reflected in orka's complement.…”
Section: Concluding Discussionsupporting
confidence: 84%
“…This type of analysis has been forwarded by Nadathur (2016) to explain the semantics of Finnish jaksaa, a sufficiency verb corresponding to Swedish orka. Nadathur's analysis is part of a discussion of implicative verbs, a discussion that is beyond the scope of our article, but some of her observations are relevant to our interpretation of orka.…”
Section: Sufficiency As An Obstacle To Ability 33mentioning
confidence: 99%
See 1 more Smart Citation
“…Having shown that the implicative reading of genuine E/T constructions is due to its bi-clausal structure, here I further characterize the nature of this implicative reading. Inspired by Schulz (2011), Baglini and Francez (2015), and Nadathur (2016), I propose that causal dependence is involved in the interpretation of genuine E/T constructions. As illustrated in (30), bi-clausal E/T constructions can be paraphrased with the use of because: their infinitival complement represents a consequence, which causally depends on the factor expressed by the comparative.…”
Section: The Semantics Of E/t Constructions: Necessary Vs Sufficientmentioning
confidence: 99%
“…The approach is inspired by Bhatt (1999), who compares actuality entailments to the characteristic complement entailments of the implicative verb manage (Karttunen 1971). Based on recent causal treatments of implicativity (Baglini & Francez 2016;Nadathur 2016), I argue that ability and manage do indeed share semantic structure, backgrounding the causal dependence of their complements on some prior action or event. On this proposal, ability and manage differ only in assertion.…”
Section: Introductionmentioning
confidence: 99%